Recent trends in insect gut immunity - Khan, Shahidul Ahmed; Kojour, Maryam Ali Mohmmadie; Han, Yeon Soo (Frontiers in Immunology, 2023)
The gut is a crucial organ in insect defense against various pathogens and harmful substances in their environment and diet. Distinct insect gut compartments possess unique functionalities contributing to their physiological processes, including immunity. The insect gut’s cellular composition is vital for cellular and humoral immunity. The peritrophic membrane, mucus layer, lumen, microvilli, and various gut cells provide essential support for activating and regulating immune defense mechanisms. These components also secrete molecules and enzymes that are imperative in physiological activities. Additionally, the gut microbiota initiates various signaling pathways and produces vitamins and minerals that help maintain gut homeostasis. Distinct immune signaling pathways are activated within the gut when insects ingest pathogens or hazardous materials. The pathway induced depends on the infection or pathogen type; include immune deficiency (imd), Toll, JAK/STAT, Duox-ROS, and JNK/FOXO regulatory pathways. These pathways produce different antimicrobial peptides (AMPs) and maintain gut homeostasis. Furthermore, various signaling mechanisms within gut cells regulate insect gut recovery following infection. Although some questions regarding insect gut immunity in different species require additional study, this review provides insights into the insect gut’s structure and composition, commensal microorganism roles in Drosophila melanogaster and Tenebrio molitor life cycles, different signaling pathways involved in gut immune systems, and the insect gut post-infection recovery through various signaling mechanisms.